PERCEPTION OF PERSONS WITH DISABILITIES GROUPS ON ACCESSIBILITY AND CONNECTIVITY OF PUBLIC TRANSPORTATION INFRASTRUCTURE IN KUALA LUMPUR, MALAYSIA - Ramli, Risha; Zainol, Rosilawati; Yaacob, Naziaty (International Journal of Property Sciences (E-ISSN: 2229-8568), 2023)
Physical and attitudinal barriers have been identified as systemic failings in public transportation, resulting in a plethora of impediments that obstruct the travel of city residents. The purpose of this study is to evaluate the perceptions of designated groups of people with disabilities (PWD) regarding the accessibility of public transportation in Kuala Lumpur, Malaysia, in order to improve the city’s public transportation system as a whole. This research strategy involves obtaining qualitative data from five distinct PWD groups, totalling twenty (20) respondents, using focus group discussion techniques four (4) individuals with physical disabilities, five (5) who are blind or partially sighted, three with learning disabilities, three older persons, and five who are deaf). The findings from the focus group discussions were organised into themes, categories, and codes. The results revealed that the PWD respondents had negative perceptions of the facilities, services, and safety of the public transportation system, particularly among those in the physical, blind, and learning disability categories. Standard operating procedures (24.12%), the design of public transportation vehicles (15.99%), and the design of transportation buildings (13.95%) were identified as the primary concerns. Additionally, the following recommendations were made; enhancing facilities and the built environment and educating the general public on the importance of creating a barrier-free environment. Understanding the perceptions of PWD toward the public transportation system in Kuala Lumpur, Malaysia paves the way for an inclusive and seamless transport system in the equitable society of Kuala Lumpur, Malaysia, thereby fostering trust and confidence in the system, especially among PWD groups.